THE PRESENT TIME, THE SAMBA-ENREDO, AND THE TEACHING OF HISTORY - Silva, Fabio Henrique Monteiro (Seven Editora, 2025)
This article seeks to analyze the importance of music, especially samba, for Teaching History in the Present Time. AbstractIn this way, we will discuss the creation of uniformity in samba schools, especially in the Vargas Era, as well as the use of this musical genre to build a national identity. Furthermore, we situate sambas from the perspective of the Present Time and their use for History Teaching.DOI: https://doi.org/10.56238/sevened2025.038-043